Microstructural characterization of oxide layers formed on Ni–20Cr–8Al alloy foam using transmission electron microscopy. (21st April 2017) - Kim, Hyung Giun; Lim, Sung Hwan
Abstract : Microstructural characterization was carried out during the pre‐oxidation of Ni–20Cr–8Al alloy foam using transmission electron microscopy (TEM). During the pre‐oxidation at 1000 °C for 1, 30, and 60 min in air, the sequential formations of NiO, NiCr2 O4, Cr2 O3, and α‐Al2 O3 1‐μm‐thick oxide layers were, respectively, characterized. Initially, during pre‐oxidization, the layers formed abnormally in an island growth mode, but they grew to be morphologically uniform after 30 min. Pores were found after only 1 min in the middle region of the oxide layers, near the Cr2 O3 layer, and then these developed into critical micro‐cracks after 60 min. Copyright © 2017 John Wiley & Sons, Ltd.